Addressing Disparities in Vision Health and Eye Care in the US (World Journal of Current Medical and Pharmaceutical Research, 2024)
Health disparities are a prevalent issue that continues to affect health outcomes. In ophthalmology, these disparities affect eye care utilization increasing the burden of eye care disorders and vision impairment/loss. Various factors contribute to disparities in vision care. They include age, gender, socioeconomic status, geographic location, and race and ethnicity. These factors make it difficult for people affected by eye conditions to access care. Addressing these disparities can help to increase eye care utilization and improve patient outcomes. Some measures that can address these disparities and increase utilization are providing patient education, increasing insurance coverage, implementing community-based eye care programs, using teleophthalmology, providing transport services, providing reminder alerts, and creating community centres that are federally funded among others. This review seeks to identify measures that can help to address disparities in vision and eye care in the US. The review also identifies drivers of health disparities in vision health and how they affect the ability to access care.